Keragaman Jenis Ikan Familia Bagridae di Sungai Nagara Desa Pandak Daun Kecamatan Daha Utara - Norma Putri Ananda Herman; Mahrudin Mahrudin; Riya Irianti (Program of Biology Education, Universitas Lambung Mangkurat, 2021)
Species diversity can be defined as the number of species among the total number of individuals of all existing species. Fish from the Bagridae family are freshwater fish with high economic value and excellent nutritional content. The purpose of this study was to describe the diversity of fish in the Bagridae family found in the Nagara River, Pandak Daun Village, North Daha District. This research was conducted in Sungai Nagara, Pandak Daun Village, North Daha Subdistrict, in August-January 2021. There are 2 zones for catching fish, namely settlements and vegetation. This research method uses descriptive method with random sampling technique. Diversity was calculated using the Shannon-Wiener diversity index. The results obtained were three types of fish in the Bagridae family, namely Mystus mumurus, Mystus nigriceps, and Mystus gulio. The highest diversity with a value of H' = 0.88 and the lowest H' = 0.72.